Design and Construction of an IoT-Based Water Pump Cart with a Sliding Solar Panel System for Agricultural Applications - Sulistiyanto Sulistiyanto; Anis Yusrotun Nadhiroh; Ilmirrizki Imanuddin (Universitas Darul Ulum, 2026)
Limited access to energy and irrigation in agricultural areas has driven the development of efficient and autonomous renewable energy-based water pumping systems. This study aims to design and implement a mobile solar-powered water pumping system integrated with an Internet of Things (IoT) platform and a sliding photovoltaic (PV) mechanism to enhance energy harvesting. The methodology includes integrated system design (mechanical, electrical, and IoT), system implementation, and experimental performance testing. The developed system utilizes an 800 Wp PV array, a 12 V 200 Ah battery, soil moisture sensors, and an IoT platform for real-time monitoring. Experimental results show that the system is capable of delivering a water discharge of approximately 1200 liters/hour and meeting irrigation demands of 1500 liters within 1.25 hours. The effective energy of 1200 Wh is sufficient to support pump consumption of around 1000 Wh per cycle, enabling stable and autonomous operation. Furthermore, field implementation indicates an increase in crop yield by approximately 36% and a reduction in harvesting time by 17%. In conclusion, the proposed IoT-based solar water pumping system with a sliding PV mechanism is technically feasible, energy-efficient, and has strong potential as a sustainable irrigation solution for small-scale farmers in remote areas.